2016
DOI: 10.1002/15-1061
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of downscaled, gridded climate data for the conterminous United States

Abstract: Weather and climate affect many ecological processes, making spatially continuous yet fine-resolution weather data desirable for ecological research and predictions. Numerous downscaled weather data sets exist, but little attempt has been made to evaluate them systematically. Here we address this shortcoming by focusing on four major questions: (1) How accurate are downscaled, gridded climate data sets in terms of temperature and precipitation estimates? (2) Are there significant regional differences in accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
117
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(131 citation statements)
references
References 45 publications
9
117
0
1
Order By: Relevance
“…The calibrated parameter values are also dependent upon the available climatic inputs to the system (Starks and Moriasi 2009). The gridded values from the Maurer et al () data set have been shown to be close to observed values (Behnke et al, ; Maurer et al, ), and herein, statistics between gridded and local precipitation were well matched (Table ). Nonetheless, differences in precipitation intensity and spatial representation would affect model calibration.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The calibrated parameter values are also dependent upon the available climatic inputs to the system (Starks and Moriasi 2009). The gridded values from the Maurer et al () data set have been shown to be close to observed values (Behnke et al, ; Maurer et al, ), and herein, statistics between gridded and local precipitation were well matched (Table ). Nonetheless, differences in precipitation intensity and spatial representation would affect model calibration.…”
Section: Discussionsupporting
confidence: 85%
“…Hydrological modelling studies have illustrated that the Maurer et al () data set can accurately simulate surface runoff as demonstrated using several large test basins forced with the gridded precipitation and temperature data (Behnke et al, ; Maurer et al, ). In fact, the Maurer et al data set consistently showed stronger agreement with observed precipitation and temperature than other gridded products, including PRISM, NLDAS2, TopoWx, and Dayment data sets (Behnke et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our model focuses on meteorological T air , which for birds in hot desert environments, is typically a minimum index of thermal stress in the absence of radiative and convective heat fluxes, and approximates the thermal conditions in a completely shaded and ventilated meteorological thermoscreen. There is also evidence that North American Land Data Assimilation System (NLDAS) and other gridded climate products often underestimate maximum temperatures by 1°C or more (22), underscoring the conservative nature of our analysis. Nevertheless, it may be possible for individuals to use cooler microsites (e.g., burrows and sites in dense vegetation) (23).…”
Section: Discussionmentioning
confidence: 82%
“…For this reason, spatial models of species distributions and biodiversity have traditionally used topographic data as a proxy variable for climatic or environmental variance, often combining them with gridded data interpolated from weather stations (Waltari, Schroeder, McDonald, Anderson, & Carnaval, ). However, recent work highlighted the wide range of methods and accuracies among products, showing that there is no “best” product and that higher‐resolution products are not necessarily more accurate (Behnke et al, ). Recent satellite missions, such as Landsat 8, Sentinel‐1, Sentinel‐2 and ICESat‐2, enable accurate and continuous acquisition of global geodiversity data in space and time (Figure b; Supporting Information Appendix A).…”
Section: Forms Of Geodiversitymentioning
confidence: 99%